2004
DOI: 10.1097/01.ju.0000107767.56680.f7
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Tumor Location on Prognosis of Transitional Cell Carcinoma of the Upper Urinary Tract

Abstract: Pelvis and ureteral TCC are not the same disease in terms of invasion and prognosis. Ureteral TCC is associated with a higher local or distant failure rate than renal pelvis TCC. A radical surgical approach including meticulous lymphadenectomy may be therapeutic in patients with invasive ureteral TCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
95
3
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(112 citation statements)
references
References 15 publications
9
95
3
5
Order By: Relevance
“…11,20 Conversely, van der Poel et al demonstrated that patients who had tumors in the renal pelvis and proximal ureter were 2.5 times more likely to die of disease compared with patients who had tumors in the distal ureter, reconfirming the data even in multivariate analyses. 10 In our series, patients with pelvic or ureteral cancers had similar survival probabilities, which were higher than those for the patients who harbored concomitant pelvic and ureteral cancers, although the data were not significant on multivariate analysis.…”
Section: Discussionmentioning
confidence: 87%
“…11,20 Conversely, van der Poel et al demonstrated that patients who had tumors in the renal pelvis and proximal ureter were 2.5 times more likely to die of disease compared with patients who had tumors in the distal ureter, reconfirming the data even in multivariate analyses. 10 In our series, patients with pelvic or ureteral cancers had similar survival probabilities, which were higher than those for the patients who harbored concomitant pelvic and ureteral cancers, although the data were not significant on multivariate analysis.…”
Section: Discussionmentioning
confidence: 87%
“…2,8,11,12,[14][15][16][17][18][20][21][22][23][24][25]29,[32][33][34] Thus, the identification of independent prognostic variables is an essential step to predict disease evolution, thus aiding surveillance strategies, and also to identify patient subgroups that might benefit from adjuvant cancer therapy. Our study is by far the largest systematic investigation of the impact of pT classification, tumor grade, as well as vascular invasion in patients with both pelvic and ureteral UCs with respect to metastasis-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…7 Our patient's UC was pathologically high grade and a pT3 lesion, with involvement of renal sinus fat via invasion through muscle. A renal pelvic location has improved survival in UC versus a ureteral primary, 8,9 though Holmang and Johansson 10 have suggested only 25% survival in high-grade pT3 upper tract UC. The UC was likely the more ominous primary lesion in this patient.…”
Section: Leveridge Et Almentioning
confidence: 99%